2018
DOI: 10.1111/mcn.12654
|View full text |Cite
|
Sign up to set email alerts
|

Complementary feeding practices among rural Bangladeshi mothers: Results from WASH Benefits study

Abstract: Inappropriate complementary feeding contributes to linear growth faltering in early childhood. Behaviour change interventions have been effective at improving practice, but few studies have investigated the effects of multicomponent integrated interventions. We conducted a cluster-randomized controlled trial in rural Bangladesh in which geographic clusters were randomized into seven arms: water treatment (W), sanitation (S), handwashing (H), water, sanitation, and handwashing (WSH), improved nutrition with inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…We saw only a modest effect on MDD at Year 1 and no effect at Year 2. In contrast, the WASH Benefits trial in Bangladesh showed an improvement in complementary feeding practices after the community health workers visited twice monthly (Jannat et al, 2018).…”
Section: Micronutrient Intakementioning
confidence: 86%
See 1 more Smart Citation
“…We saw only a modest effect on MDD at Year 1 and no effect at Year 2. In contrast, the WASH Benefits trial in Bangladesh showed an improvement in complementary feeding practices after the community health workers visited twice monthly (Jannat et al, 2018).…”
Section: Micronutrient Intakementioning
confidence: 86%
“…We saw only a modest effect on MDD at Year 1 and no effect at Year 2. In contrast, the WASH Benefits trial in Bangladesh showed an improvement in complementary feeding practices after the community health workers visited twice monthly (Jannat et al, ). Additionally, other BCC programmes that have been effective at improving complementary feeding outcomes have had a mass media component, which our programme lacked (Sanghvi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…There may be concerns that the integration of too many health and hygiene messages within specific caregiver groups could be overwhelming for both facilitators and participants. However, the call for an improved integration of services, as well as evidence from recent studies [53], demonstrates that such integration is an effective route for improving hygiene practices in the lowest quintile of caregivers by education.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the nutrition intervention, which focused on the timely introduction of diverse complementary foods, resulted in a higher dietary diversity score at both time points (Jannat et al, 2018) and high adherence to lipid‐based nutrient supplementation recommendations (Luby et al, 2018). The present data suggest that parents prioritized feeding the promoted nutritious foods or lipid‐based nutrient supplements over commercially available sweet, salty, or packaged snack foods to their children.…”
Section: Discussionmentioning
confidence: 99%
“…This model was used to assess the association among children from the nutrition or nonnutrition arms and controls separately. We examined that the association between snack food consumption and dietary diversity in the nutrition arm and other arms as dietary diversity was similar among children from control and nonnutrition arms (Jannat et al, 2018). Food insecurity was measured using WHO Household Food Insecurity Access Scale (Coates, Swindale, & Bilinsky, 2007).…”
Section: Methodsmentioning
confidence: 99%